Feminist Utopias, Queerness and Paul Goodman. Issue 1 (November 2020) - Grassi, Samuele
The question of whether a (queer) politics of utopia can be located in the past, the future or the present conjures a set of ambivalences and dichotomies, of which the creativity–negativity debate and the (non)future of neoliberalism are cogent for feminist praxis. Convergences can be traced between understandings of utopia grounded in everyday experimentation and queer feminist critiques of normativity as a life project as well as an ongoing educational project. This article dissects social critic, psychologist, poet, novelist and anarchist Paul Goodman's essay 'The politics of being queer' (1969), reading it through a queer feminist lens in order to shed new light on his 'buried conversations' with feminism. Mindful of and in opposition to Goodman's controversial avowal of 'masculinities'—most notably in his Growing Up Absurd (1960)—the article situates his idea(s) of freedom-autonomy and the disidentifications he proposed—with gay liberation agendas/movements, with bisexuality, with 'masculinity'—within a wider feminist educational/pedagogical project of experimenting with utopia in the here and now. Goodman's calls for a liberated society left us a utopian imaginary for engaging with an embodied politics for the present—for teaching, educating, loving and living differently.